(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the modern educational environment, digital technologies have transformed the way learners engage with content, instructors, and themselves. One critical aspect of this transformation is the automation of self-assessment processes. This article explores how digital evaluation tools facilitate self-regulated learning by enabling students to assess their own performance efficiently and objectively. The paper highlights the pedagogical value, implementation strategies, and challenges of using digital platforms to support self-assessment, particularly in higher education systems using credit-modular models.